No i'm a stork - Αρκάς (Flying starts, 1992)
NO! I AM A STORK! The tittle sparrow vehemently rejects his own species because there is no future in being a little sparrow. The most you can hope for is to become a big sparrow - which is exactly what his father is, and that is the last thing in the world he wants to end up being! Another volume in the series Flying Stars by Greek cartoonist Arkas, whose little winged tyrant and harried father constantly quarrel over questions of life, beauty, freedom and the importance of self-acceptance as they fly over gloomy city skylines.